2012
DOI: 10.1161/circep.112.974386
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Effect of β-Blockers in Preventing Vasovagal Syncope

Abstract: Background-β-blockers have little effectiveness in preventing vasovagal syncope in unselected populations, but they might be effective in older patients. We determined whether β-blockers prevent vasovagal syncope in an age-related fashion. Methods and Results-Two populations were studied. A proportional hazards analysis was performed on an observational cohort study of 153 patients with vasovagal syncope, 52 of whom received β-blockers. A multivariable proportional hazards model stratified by center was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 47 publications
1
34
1
2
Order By: Relevance
“…A recent meta-analysis demonstrated a statistically significant difference in response in those aged <42 years and ≥42 years (test of interaction P=0.007). 86 β-Blocker use reduced syncope recurrence in those aged ≥42 years by 48% but increased the risk in those aged < 42years by 58%. 86 Accordingly, the cautious use of β-blockers is reasonable in older patients with vasovagal syncope, particularly when hypertension in present.…”
Section: Beta Blockersmentioning
confidence: 97%
“…A recent meta-analysis demonstrated a statistically significant difference in response in those aged <42 years and ≥42 years (test of interaction P=0.007). 86 β-Blocker use reduced syncope recurrence in those aged ≥42 years by 48% but increased the risk in those aged < 42years by 58%. 86 Accordingly, the cautious use of β-blockers is reasonable in older patients with vasovagal syncope, particularly when hypertension in present.…”
Section: Beta Blockersmentioning
confidence: 97%
“…A multicenter randomized controlled study of metoprolol showed no benefit overall, but suggested benefit in patients older than 42 years. 57,58 This theory will be the subject of a further randomized trial of metoprolol in this age group (POST 5 [Prevention of Syncope Trial 5], RS Sheldon, personal communication, June 2013). Fludrocortisone is commonly used in VVS management, but there have been no published randomized data in adults, although the POST II study 59 in abstract form suggests that there may no benefit at all (http://www.theheart.…”
Section: Discussionmentioning
confidence: 99%
“…No difference was observed in recurrence of syncope, even when stratified by age and isoproterenol response during tilt test. Subsequent pooled analysis with non-randomized patients found a significant interaction of beta-blockers with age, suggesting benefit after age 42, and potential harm in younger patients [8].…”
Section: Effectiveness and Study Designmentioning
confidence: 98%